1999
DOI: 10.1046/j.1469-7580.1999.19410033.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascularisation in adipose depots surrounding immune‐stimulated lymph nodes

Abstract: We report a change in the vascularisation of the adipose depots surrounding the popliteal lymph node that has, and the contralateral node that has not, been exposed to a simulated immune challenge. The percentage of the depot that consists of vessels, as measured by image analysis, decreases over a period of 2 d after immune stimulus, then increases in a biphasic manner over the next 2-3 wk. By 1 mo after the stimulus, the vascularisation has returned to baseline values. The adipose tissue surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…8 Immunocytochemistry with anti-rat mononuclear phagocyte in the adipose tissue of tumour-bearing rats (A) and control reaction (B) studies found no variation between the constitutive secretion (Eriksson et al 2000) or gene expression (Montague et al 1997) between these latter depots. However, a greater expression of TNF receptors was found in the mesenteric adipocytes adjacent to lymph nodes (Macqueen et al 1999). We were not able to find studies on the heterogeneity of TNFα secretion by adipose tissue during cachexia, and hence we conclude that this is the first attempt to characterize interdepot variation in this parameter.…”
Section: Discussionmentioning
confidence: 52%
“…8 Immunocytochemistry with anti-rat mononuclear phagocyte in the adipose tissue of tumour-bearing rats (A) and control reaction (B) studies found no variation between the constitutive secretion (Eriksson et al 2000) or gene expression (Montague et al 1997) between these latter depots. However, a greater expression of TNF receptors was found in the mesenteric adipocytes adjacent to lymph nodes (Macqueen et al 1999). We were not able to find studies on the heterogeneity of TNFα secretion by adipose tissue during cachexia, and hence we conclude that this is the first attempt to characterize interdepot variation in this parameter.…”
Section: Discussionmentioning
confidence: 52%
“…The results are not consistent with the long-established assumption (Clandinin et al 1991) that the precursors of PL of newly formed cells are derived directly from the diet via blood-borne lipids. Vascularisation of the perinodal adipose tissue increases under chronic immune stimulation, but the process is very slow compared with the timescale of this experiment (MacQueen et al 1999). Increased perfusion of both the inflamed lymph node and its surrounding adipose tissue would obliterate most of the changes induced by the supplemented diets in the inflamed tissues, replacing them with fatty acids derived from the plain diet.…”
Section: Paracrine Relationship Between Adipose and Lymphoid Tissuesmentioning
confidence: 86%
“…1994; Schling & Löffler, 2002). Vascularization of perinodal adipose tissue increases slowly during chronic inflammation (MacQueen et al. 1999).…”
Section: Discussionmentioning
confidence: 99%